Clinical Presentations and Characteristics of NSAIDs Hypersensitivity in a Tertiary Care Hospital in Indonesia: A Case Series - Nurmesa A; Zakiyah N; Insani WN (International Medical Case Reports Journal)
Adi Nurmesa,1,2 Neily Zakiyah,1,3 Widya Norma Insani1,3 1Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Bandung, 40132, Indonesia; 2Department of Pharmacy, Dr Rivai Abdullah Regional General Hospital, Banyuasin, 30961, Indonesia; 3Center of Excellence for Pharmaceutical Care Innovation, Universitas Padjadjaran, Bandung, 40132, IndonesiaCorrespondence: Neily Zakiyah, Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Bandung, 40132, Indonesia, Email neily.zakiyah@unpad.ac.idAbstract: Non-steroidal anti-inflammatory drugs (NSAIDs) are widely administered in all age groups due to their effectiveness in reducing fever, relieving pain, and reducing inflammation. However, they have also been identified as the second most common cause of drug-induced hypersensitivity reactions, after beta-lactam antibiotics. Adverse reactions to NSAIDs can range from expected pharmacological side effects such as gastritis to severe allergies, including anaphylaxis. It is important to distinguish true hypersensitivity reactions from other side effects to ensure proper management and patient safety. Four patients aged 35– 60 years were treated with NSAIDs for pain management and subsequently developed hypersensitivity reactions to NSAIDs such as ketorolac, ketoprofen, and diclofenac sodium in the type of allergic reactions such as NSAIDs-induced urticaria/angioedema (NIUA). This case series provides valuable insights into the clinical presentations and potential mechanisms of NSAID hypersensitivity in the documented cases in one of the hospitals in Indonesia. It highlights important areas for future investigation, including the need for larger, controlled studies to better understand incidence, risk factors, and generalizability to broader populations.Keywords: hypersensitivity, NSAID, pain, analgesic, allergic reaction